2017
DOI: 10.1182/bloodadvances.2016001552
|View full text |Cite
|
Sign up to set email alerts
|

ATG in allogeneic stem cell transplantation: standard of care in 2017? Counterpoint

Abstract: This article has a companion Point by Bacigalupo.Despite improvements in HLA matching, quality control measures, and supportive care used in hematopoietic stem cell transplantation (HSCT), graft-versus-host disease (GVHD) remains a common cause of morbidity and mortality in transplant recipients. 1 The primary goal of HSCT is to cure the underlying hematological disorder with as little residual disability as possible. Achieving this goal requires supporting the patient through a conditioning regimen and its as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…All patients received ATG, which could have contributed to the lower incidence of severe GVHD. The use of ATG reflects a form of in vivo T cell depletion, which concomitantly depletes host T cells that survive the conditioning regimen and reduces the risk of rejection while depleting newly infused donor T cells, thereby potentially reducing GVHD [41]. In this study, we used the same low-dose PT-CY regimen for GVHD prophylaxis as has been reported for patients with FA, but we continued immunosuppressive therapy with cyclosporine and MMF for 6 months and then tapered it gradually in those without active GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…All patients received ATG, which could have contributed to the lower incidence of severe GVHD. The use of ATG reflects a form of in vivo T cell depletion, which concomitantly depletes host T cells that survive the conditioning regimen and reduces the risk of rejection while depleting newly infused donor T cells, thereby potentially reducing GVHD [41]. In this study, we used the same low-dose PT-CY regimen for GVHD prophylaxis as has been reported for patients with FA, but we continued immunosuppressive therapy with cyclosporine and MMF for 6 months and then tapered it gradually in those without active GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…The most common ATG formulations include Thymoglobulin (Genzyme-Sanofi, Cambridge, MA) and ATLG Grafalon (ATLG; previously referred to as ATG Fresenius; Neovii Pharmaceuticals AG, Rapperswil, Switzerland), which are generated by immunizing rabbits with human thymocytes or Jurkat T lymphoblastoid cells, respectively. The relative efficacies of these formulations have not been compared head-to-head in vivo, and current recommended HCT dosages for these formulations differ by nearly 10-fold despite in vitro evidence of similar T cell cytotoxicity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…37 Another potential variable is the difference in ATG formulations (thymoglobin versus Grafalon) used across the studies. 40,41 It is unknown whether in vivo TCD is comparable between these 2 formulations because of the absence of dose equivalence and head-to-head comparisons between thymoglobin and Grafalon. In a meta-analysis of prospective studies, Gagelmann et al showed that Grafalon was associated with improved GVHD (acute and chronic) rates compared with thymoglobin.…”
Section: Discussionmentioning
confidence: 99%